1999
DOI: 10.1038/sj.leu.2401241
|View full text |Cite
|
Sign up to set email alerts
|

Internal tandem duplication of the FLT3 gene and clinical evaluation in childhood acute myeloid leukemia

Abstract: We analyzed tandem duplication in the juxtamembrane (JM) domain of the FLT3 (FMS-like tyrosine kinase 3/FLK2, CD135) gene in 94 children with acute myeloid leukemia (AML) and evaluated its correlation with clinical features. Longer polymerase chain reaction (PCR) products were observed in five patients; 1/3 of M0, 1/9 of M1, 1/39 of M2, 1/9 of M3 and 1/12 of M5. The sequence analyses of abnormal PCR products showed that all the abnormal products were derived from tandem duplications involving the JM domain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 23 publications
7
120
1
Order By: Relevance
“…Frequencies reported for the Japanese childhood AML population vary between 11% (Kondo et al, seven out of 64 cases studied) 21 and 5.3% (Iwai et al, five out of 94 cases studied). 22 A possible explanation for the observed lower incidence in childhood AML could be that Flt3/ITDs results from genomic instability as was postulated by the latter authors. Kiyoi et al 23 have shown that in COS cells, transduced with cDNA encoding for Flt3/ITDs, elongation of the JM domain and ligandindependent dimerization of the mutant receptor occurs, thus resulting in a constitutive activation.…”
Section: Introductionmentioning
confidence: 89%
“…Frequencies reported for the Japanese childhood AML population vary between 11% (Kondo et al, seven out of 64 cases studied) 21 and 5.3% (Iwai et al, five out of 94 cases studied). 22 A possible explanation for the observed lower incidence in childhood AML could be that Flt3/ITDs results from genomic instability as was postulated by the latter authors. Kiyoi et al 23 have shown that in COS cells, transduced with cDNA encoding for Flt3/ITDs, elongation of the JM domain and ligandindependent dimerization of the mutant receptor occurs, thus resulting in a constitutive activation.…”
Section: Introductionmentioning
confidence: 89%
“…The most common type is an intern tandem duplication (ITD) in exons 14 and 15 (previously known as exons 11 and 12) that map to the JMD, seen in 25-35% of adult and 12% of childhood AML. [5][6][7][8][9][10][11][12][13][14][15][16] These ITD, and deletion or insertion/deletion mutations affecting the JMD, are sometimes called length mutations (LM) in the literature. Here, we use the term ITD to refer to all JMD mutations.…”
Section: Flt3mentioning
confidence: 99%
“…Here, we use the term ITD to refer to all JMD mutations. [13][14][15][16] The length of the duplicated JMD region varies from 3 to 400 nucleotides but, despite this heterogeneity, the resultant transcripts are always in-frame. 17 The second most common type of FLT3 mutation is a missense point mutation in exon 20, within the activation loop (AL) of the tyrosine kinase domain (TKD), found in 5-10% of AML patients.…”
Section: Flt3mentioning
confidence: 99%
“…5,6 The majority of clinical studies of the Flt3 ITD in both adults [7][8][9][10][11][12] and children 13,14 have shown that the presence of a single Flt3 ITD allele is an independent poor prognostic factor in AML, particularly in nonpromyelocytic AML. However, one of these studies 8 suggested that the presence of the Flt3 ITD only tends to influence prognosis when the PCR-defined ratio of the ITD allele to the wild-type allele (the Flt3 allelic ratio) is relatively high, while another study found that the adverse prognostic impact of the ITD is only observed if both wild-type alleles are affected.…”
Section: Introductionmentioning
confidence: 99%